Studies on the antifungal effect of cymbopogon nardus (serai wangi) on several fungi and yeasts - Zainuddin, Nik Aida Diana Nik (2004)
Antifungal studies of Cymbopogon nardus were carried out against several different fungi and yeast. Cold extraction method employing organic solvents was used in this study. The filtered aqueous methanolic extract of the leaves was sequentially extracted with n-hexane, chloroform and ethanol respectively. Candida albicans, Candida g/abrata, Candida tropicalis and Cryptococcus neoformans were selected as test organisms. The chloroform extracts of Cymbopogon nardus was active against Candida albicans, Candida glabrata and Candida tropicalis giving a clear zone of 0. 7- 0.8 em at different concentrations (0.01 mg/ml, 0.1 mg/ml and 1.0 mg/ml). The nhexane, ethanol and methanol extract did not show any inhibitory activity against the microorganisms tested except for Candida glabrata, where a clearing zone of 0.6-0.9 em was noted for the ethanol and methanol extracts at different concentrations. nHexane, chloroform, ethanol and methanol extracts were active against Cryptococcus neoformans at all the concentration tested. However, the growth inhibitory effect of all the extracts are insignificant compared to the antibiotic Amphotericin B.